Economic and Socio-Cultural Development Dimension—Two Lake-Protected Areas’ Sustainability: A Case of Hungary and Serbia - Tabak, Brankica; Trišić, Igor; Štetić, Snežana; Nechita, Florin; Ilić, Mirjana; Obadović, Milica; Dobrescu, Ada Ioana (MDPI AG, 2025)
The Balaton Uplands National Park (BUNP) and Palić Nature Park (PNP) have significant tourism potential for the development of specific tourism forms. These lake destinations offer not just natural features but also a developed infrastructure and a variety of events that are important to the ethno-social values of the local population. In this paper, the sociocultural and economic aspects of these locations are studied. Researching these two dimensions of sustainable tourism development (STuD) is important for tourism planning, growth, and control of STuD. This article’s research focuses on socio-cultural and economic elements that are critical to the growth of tourism (ToD). They are analyzed through revenue, employment, visitor spending, cultural and culinary marketing, events, and other aspects of this eco-sensitive tourist attraction. The study’s noteworthy findings demonstrate the importance of economic and socio-cultural elements for ToD and their substantial influence on the institutional and environmental aspects of sustainability. The quantitative method involved surveying visitors to these two protected areas. A total of 810 visitors participated in this research. Respondents expressed the importance of these two sustainability groups. Also, the results of the research indicate that economic and socio-cultural factors influence the respondents’ satisfaction to a significant extent. The research findings may be significant in the creation of plans for the growth of tourism.
Keywords: sustainable tourism; prism of sustainability; visitor satisfaction; protected areas